Somatotipo en futbolistas mexicanos profesionales de diferente nivel competitivo - Zuñiga Galaviz, Uriel (2018)
To identify the somatotype of professional soccer players according to the competitive level of the Mexican soccer league (1st division, 1st «a» division, 2nd division and 3rd division), and to obtain the somatotype altitudinal distance (SAD) and the somatotype attitudinal mean (SAM). Method: 78 professional soccer players belonging to the Mexican soccer league were evaluated. They were grouped in four groups (1st division, 1st «a» division, 2nd division, and 3rd division) according to the level of competition. Somatotype was obtained using 10 anthropometric variables (Carter & Heath, 1990); likewise, SAD and SAM were calculated. Results: Significant differences were found in age between the four divisions groups (p<0.01). We did not found significant differences between 1st division and 1st «a» division regarding somatotype. The somatotype distance between 1st division and 1st «a» division was lower than one; all other possible combinations between the groups were higher than one. Conclusion: Somatotype changes according to the level of performance, which can be explained by the differences in age and by the differences in the demands of training and competition of each division.